Clinicopathologic Assessment of Monoclonal Immunoglobulin-associated Renal Disease in the Kidney Allograft: A Retrospective Study and Review of the Literature. Issue 7 (July 2020) - Kamal, Jeanne; Khairallah, Pascale; Crew, Russell J.; Ye, Xiaoyi; Swanson, Sidney J.; Kudose, Satoru; Park, David C.; Appel, Gerald B.; Markowitz, Glen S.; D'Agati, Vivette D.; Batal, Ibrahim
Abstract : Background: Monoclonal immunoglobulin (MIg)-associated renal disease (MIgARD) comprises a group of disorders caused by direct deposition of paraproteins in the kidney. Allograft MIgARD is infrequently encountered and poorly characterized. Methods: First, we assessed our allograft biopsies diagnosed with MIgARD between 2007 and 2018. The cohort included the following 26 patients: proliferative glomerulonephritis with MIg deposits (PGNMID) (n = 13), AL amyloidosis (n = 5), light chain deposition disease (n = 5), light chain proximal tubulopathy (n = 2), and light chain cast nephropathy (n = 1). Second, we conducted a literature review to evaluate the rare non-PGNMID entities. We identified 20 studies describing 29 patients that were added to our cohort (total n = 42). Results: Part 1: Patients' median age was 55 years; 31% were women, and 19% were blacks. Twelve patients (46%) lost their grafts at a median of 8 months after diagnosis. Compared to non-PGNMID, PGNMID patients had lower frequency of detectable paraproteins (31% versus 92%, P = 0.004) and hematologic neoplasms (23% versus 77%, P = 0.02). Within PGNMID group, 6 patients changed their apparent immunofluorescence phenotype between monotypic and polytypic, while all 3 patients with hematologic neoplasms had substructure on electron microscopy. Part 2: Whereas light chain cast nephropathy occurred the earliest and had the worst graft survival, AL amyloidosis occurred the latest and had the best graft survival. Conclusions: MIgARD in the kidney allograft is associated with poor prognosis. While posttransplant PGNMID can change its apparent clonality by immunofluorescence supporting oligoclonal immune responses, the presence of deposit substructure is an important indicator of underlying hematologic neoplasm. Non-PGNMID are often associated with hematologic neoplasms and varied prognosis. Abstract : Supplemental Digital Content is available in the text.